Heat and mass transfer in a vertical channel flow through a porous medium in the presence of radiation - Guria, M. (Zielona Góra: Uniwersytet Zielonogórski)
An analysis is made of heat and mass transfer in a three dimensional flow between two vertical porous plates through a porous medium. Analytical solutions have been obtained using the perturbation technique. The effect of non-dimensional parameters on velocity, temperature and concentration field are shown graphically.
Keywords: mass transfer; permeability; porous medium; periodic suction; radiation